The Effect of Giving Moringa Leaf Tea and Honey on Increasing Breast Milk (ASI) Production in Postpartum Mothers on Days 1-7 in the Working Area of the Handil Baru Community Health Center - Rafika Nur Indasar; Novi Pasiriani; Faridah Hariyani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Breast milk is the best food for babies, but the rate of exclusive breastfeeding is still low due to insufficient breast milk production, so there is a need to provide intervention in the form of giving Moringa leaf tea and honey which contain nutrients (energy, carbohydrates, protein) which function as energy. the posterior pituitary produces the hormones oxytocin and prolactin and increases breast milk production. To determine the effect of giving Moringa leaf tea and honey on increasing breast milk (ASI) production in postpartum mothers on days 1-7 in the Handil Baru Community Health Center working area. This type of research uses quasi-experimental research design, namely nonequivalent control group design. Production of breast milk (ASI) after being given Moringa leaf tea and honey to postpartum mothers on days 1-7 of all respondents was 100% sufficient breast milk.